2017
DOI: 10.1002/2016jd025856
|View full text |Cite
|
Sign up to set email alerts
|

Predictable patterns of the May–June rainfall anomaly over East Asia

Abstract: During early summer (May–June, MJ), East Asia (EA) subtropical front is a defining feature of Asian monsoon, which produces the most prominent precipitation band in the global subtropics. Here we show that dynamical prediction of early summer EA (20°N–45°N, 100°E–130°E) rainfall made by four coupled climate models' ensemble hindcast (1979–2010) yields only a moderate skill and cannot be used to estimate predictability. The present study uses an alternative, empirical orthogonal function (EOF)‐based physical‐em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 74 publications
(88 reference statements)
0
18
0
Order By: Relevance
“…Despite the growing evidence in the literature of the potential value of considering EASM rainfall prediction on subseasonal timescales, the vast majority of predictability studies has focused only on the seasonal mean rainfall. Those that have considered subseasonal prediction (including Kim et al, 2008;Wang et al, 2009;Yim et al, 2014Yim et al, , 2016Xing et al, 2016Xing et al, , 2017Xing and Huang, 2019) have found better skill when using physical-empirical models compared with dynamical models, even with multi-model ensembles. Generally, these studies have demonstrated value in separating predictions for the early and late summer season rainfall, with greater skill at earlier lead times generally being demonstrated for the early summer (May-June).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the growing evidence in the literature of the potential value of considering EASM rainfall prediction on subseasonal timescales, the vast majority of predictability studies has focused only on the seasonal mean rainfall. Those that have considered subseasonal prediction (including Kim et al, 2008;Wang et al, 2009;Yim et al, 2014Yim et al, , 2016Xing et al, 2016Xing et al, , 2017Xing and Huang, 2019) have found better skill when using physical-empirical models compared with dynamical models, even with multi-model ensembles. Generally, these studies have demonstrated value in separating predictions for the early and late summer season rainfall, with greater skill at earlier lead times generally being demonstrated for the early summer (May-June).…”
Section: Introductionmentioning
confidence: 99%
“…Although the EASM rainy season typically extends from May to September, North China mainly receives rain during July-August, with climatological features different from those in the other East Asian regions (Xing et al 2017). Therefore, this paper focuses on the monthly rainfall in July and August.…”
Section: Datamentioning
confidence: 99%
“…East Asian subtropical frontal rainfall is sensitive to the strength and location of the western Pacific subtropical high (WPSH), which is largely determined by the local atmosphere-ocean interaction (Wang et al, 2017a). Some studies have further shown that the origins and predictabilities of East Asia rainfall in early summer and late summer are obviously different (Wang et al, 2009;Xing et al, 2016Xing et al, , 2017.…”
Section: Introductionmentioning
confidence: 99%